SAR Interferometry and Tomography: Theory and Applications - PASCAZIO, Vito; Fornaro, Gianfranco (Academic Press, Elsevier, 2014)
Synthetic Aperture Radar (SAR) is among of the most used remote sensing systems for Earth observation and has wide application in security in both marine and terrestrial environments. The last decade has been a period of extraordinary development of SAR systems with an impressive growth in the number of launch and operational deployment of spaceborne SAR remote sensing systems. Enabling an extensive range of new applications is the advent of several very high resolution spaceborne SARs, such as TerraSAR-X/Tandem-X and the COSMO-SKYMED constellation. Very fine details of Earth surface are provided on a regular basis by data acquired and processed by those sensors. A significant contribution to the desire to field such systems has been the development of coherent processing techniques, in particular interferometry, that have dominated SAR applications since their first demonstration in the late 70's and early 80's. Evidence of the importance and versatility of radar interferometry is its application to such diverse area as the monitoring of volcanoes, earthquakes, landslides, ice sheet motion and anthropogenic sources such as ground pumping of water and oil. Development of innovative processing techniques, like permanent scatterer interferometry, polarimetric-interferometry and tomography have expanded the number of applications and data sets that can be successfully exploited. For example, permanent scatterer interferometry and tomography have revolutionized what can be done by SARs in urban environments. In this article we aim to provide a description of the some of the major developments in SAR interferometry and SAR tomography with particular emphasis on the digital signal processing aspects. We will illustrate SAR tomography using urban and infrastructures applications although it has other applications such as in forest and ice structure. Examples of applications of interferometry and tomography are provided to demonstrate the practical usefulness of the technological advances occurring on both the SAR ...